Temporary hair loss after injection of hyaluronic acid filler. (15th September 2021) - van den Elzen, Helga; Schelke, Leonie; Velthuis, Peter
Abstract: Background: Compromised blood flow after filler injection is generally thought to result from intra‐arterial obstruction. Aims: To test this hypothesis. Patient: A case presented with the clinical picture of reduced arterial blood flow after hyaluronic acid filler injection in the temporal region and subsequent hair loss. Method: Clinical and ultrasound (US) assessments as well as ultrasound guided hyaluronidase injection were performed. Result: Blood flow was restored and hair loss proved to be temporary. Conclusion: There are many arguments to conclude that the problem did not result from intra‐arterial occlusion, but rather from outside compression of the artery.